Colonial citizenship and everyday transnationalism : an immigrant's story - Innes, Alexandria J. (Abingdon, Oxon : Routledge, 2020)
This book uncovers the contradictions and convergences of racism, decolonisation, migration and living international relations that were shaped by the shift from colonialism to postcolonialism and from nationalism to transnationalism between the 1950s and the present. It takesup the story of Nicholaos Charalambou Kanaris, a colonial migrant to the UK from Cyprus, as a reflection on how the everyday lives of minor figures offer an unexplored window into international relations. The research uncovers and offers insight into the complexities and messiness of everyday life and of (trans)national identities as they are lived and have been lived at the heart of imperial, colonial and postcolonial systems and processes. The innovative methodological approach adopts memoirs gathered through a series of life-narrative interviews and is guided by theories of minor transnationalism that look to foreground horizontal relations between minor figures. Various themes of international relations are examined through the lens of Nicholaos' story and his family life, including colonialism, geopolitics, citizenship, security, migration and transnationalism. Examining how these themes play out in everyday life permits his practice and lived experience to theorise the international politics of colonialism, migration and citizenship. This book argues that Politics and International Relations can benefit from a transnational approach and offers a method of theory-in-practice for exploring the everyday experience of transnationalism, through the methodology of life-narrative and memoir.
Introduction Part I: Colonial Migration; Becoming Transnational Excerpt 1: The stock I come from 1. The Global and Local Politics of Everyday Life in 1950s Famagusta Excerpt 2: Improvise to survive 2. Colonial Subjectivity, Colonial Immigration, and National Identity Excerpt 3: Going down the pits 3. Ontological Security, Affective Environments and the Future Part II: Transnational Family Life 4. Theorising the Transnational Family in International Relations 5. Transnational Citizenship: From Wallsend to Paphos Conclusion Post Script.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: POLITICAL SCIENCE / General; Transnationalism; Emigration and immigration -- Social aspects; Postcolonialism -- Social aspects; Immigrants -- Cultural assimilation; Kanaris, Nicholaos Charalambour, -- 1934-; Cypriots -- Great Britain -- Biography